Answer:
The equation of the perpendicular bisector is 2x + 3y - 3 = 0
Explanation:
* How to find the equation of a line from two points (x1 , y1)
and (x2 , y2) lie on it
- Find the slope of the line using the rule
The slope (m) = (y2 - y1)/(x2 - x1)
- Use the rule of the equation y - y1 = m (x - x1), where m is
the slope of the line and (x1 , y1) is a point on the line
* Remember if two line are perpendicular, then the product of
their slopes = -1, that means one of them is an additive inverse
and multiplicative inverse to the other
# Ex: if the slope of a line is a/b, then the slope of the
perpendicular to it is -b/a
* Now lets read the problem, we need the equation of the
perpendicular bisector to the line that passes through the
points (2 , 4) and (-2 , -2)
- Find the slope of the line in the graph by using the given points
# m = (-2 - 4)/(-2 - 2) = -6/-4 = 3/2
∴ The slope of the perpendicular line = -2/3 ⇒ multiplicative
inverse and additive inverse of it
* Bisector means intersect it in the mid-point of the given line
- The rule of the mid-point is [(x1 + x2)/2 , (y1 + y2)/2]
∴ The mid-point of the line is [(2 + -2)/2 , (4 + -2)/2] = (0 , 1)
* Now we have the slope and a point on the line, to find the
equation of the perpendicular bisector its slope is -2/3 and
a point (0 , 1)
∴ The equation: y - 1 = -2/3 (x - 0)
The equation : y - 1 = -2/3 x ⇒ Multiply both sides by 3
The equation : 3y - 3 = -2x ⇒ collect x , y in the same side
The equation : 2x + 3y - 3 = 0
* The equation of the perpendicular bisector is 2x + 3y - 3 = 0